SISTEM REKOMENDASI PEMILIHAN ART SHOP MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DAN ELIMINATION ET CHOIX TRADUISANT LA REALITE (STUDI KASUS WILAYAH KABUPATEN BADUNG BALI) - I Dewa Ketut Satria Wahyu Perdana; Dyah Erny Herwindiati; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Art shops in Bali are developing, but only a few areas are known to tourists as central art shops. Lack of knowledge of tourists about art shops in an area, tourists have to go around to many art shops to get an art shop that matches the tourist criteria. To overcome the problems, it is necessary to design a computerized system, because with a computerized system, finding an art shop in the Badung Regency, Bali will be easier and faster. A computerized system can also help to see which art shop recommendations are available in an area, and what criteria are available in the art shop. The decision support system (Decision Support System / DSS) is one type of application system that is very well known among organizational management. DSS is designed and created to help management in the decision-making process and the quality of decision making, one of which is Multi Attribute Decision Making. In Multi Attribute Decision Making, there are many decision support system methods, such as the Analytical Hierarchy Process (AHP) and Elimination Et Choix Traduisant la Realité (ELECTRE). In this decision support system, it uses two methods, namely the Analytical Hierarchy Process (AHP) to determine the weight of each criteria and the next process is to rank the best attributes using the Elimination Et Choix Traduisant (ELECTRE) method. With this method, it is hoped that it can make it easier to find an Art Shop that fits the desired criteria.